MITOLOGI DALAM TEORI GENETIK KONRAD Z. LORENZ: PERSPEKTIF PENDIDIKAN ISLAM - Hamlan Andi Baso Mala; Andi Makarma (ISTIQRA: Jurnal Hasil Penelitian, 2021)
This paper criticizes Konrad Lorenz's genetic theory which says humans are social animals. Lorenz describes animal social behavior which is implemented in human social behavior. The argument built by Lorenz focuses on human social behavior due to biological causes. This paper is a discourse analysis in the study of literature by using the approach of social and Islamic education theories. The findings of this study, first; Lorenz is of the view that human social behavior originates from genetics. He studied animal social phenomena to be applied to human social behavior which has a different biological structure from animals. Second; Lorenz's argument that humans are the same as animals because their innate instincts are very debatable. Third; From the perspective of Islamic education, Lorenz argues is very disproportionate because the biological structure of humans is different from the biological structure of animals. The weakness of Lorenz's genetic theory of human behavior is that it places too much emphasis on the biological aspect alone or in the narrative "humans are social animals", this theory can be accepted as mythology in the paradigm of academic studies. Keywords: